Effect of Hydrogen on Conductivity of Metals; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Larionov V. V. Vitaliy Vasilyevich; Xu Shupeng; Shi K.; Kroning M. X. (Materials Science and Technologies, 2015)
Title screen